A Systematic Review of Error Gravity Articles: Themes of Leniency, Perceptions, and Hierarchies - Maharjan, Laxmi Bahadur (Mangal Research Journal, 2024)
This systematic review synthesizes findings from various studies published before 2000 to understand the frameworks and criteria researchers use to assess error gravity. The study aims to explore how different types of errors are evaluated regarding their severity and impact, as well as perceptions in spoken and written language, ultimately establishing hierarchy of errors. I selected thirty-one articles on error gravity in language assessment published from 1969 to 1999 using a purposive sampling method, focusing exclusively on studies that directly address the evaluation of error gravity. The sources for the articles in my study included various journals, dissertations, monographs, ERIC documents, and conference proceedings. I conducted an in-depth study of these articles, resulting in four themes: Perceptual Dichotomy: Leniency vs. Seriousness of Errors, Perception of Errors in Spoken Communication, Perception of Errors in Written Compositions and Establishing Hierarchies of Error. The review study revealed that tolerance toward ESL errors has become a distinctive characteristic of native speakers, reflecting perceptual trends closely tied to their native-speaker identity. The study concluded that native speakers perceive errors in a hierarchy based on severity. However, the concept of a "universal hierarchy of errors" lacks conclusive evidence. McCretton and Rider (1993) emphasized that these hierarchies are shaped by evaluators’ educational backgrounds, challenging the idea of inherent universality.